Plastic & Plankton Abundance & Composition in waters off South China Sea - Lee, Yong Jun (Universiti Malaysia Sarawak (UNIMAS), 2022)
Plastic pollution is a worldwide issue that has been taking place across terrestrial and aquatic ecosystems since the beginning of its mass production dated back in the 1950s. Every year, the abundance of marine plastic debris accumulates and increases significantly to cause harm toward the marine biota as they stay persistently within the marine environment. Hence, the South China Sea waters were selected as a potentially affected ecosystem to study the relationship between the abundance and composition of both plastic and plankton considering lack of studies in the deep-sea region. In this research, plastic composition and abundance were assessed by compartments namely the (particles, fragments, and fibers). Furthermore, the water samples were observed under the Differential Interference Contrast compound microscope to help identify the plankton composition according to their genus in the respective groups. The cell abundance of plankton was calculated using the Sedgewick rafter counting chamber of unit individual per liter. A strong negative correlation between the abundance of plastic and plankton was established by utilizing the Pearson correlation test analysis. The finding of this study had further implicated the negative effects of plastic particles on the existing plankton community in SCS waters.